2022
DOI: 10.1186/s12967-022-03602-5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbiome in chronic kidney disease: what is its connection to diabetes, hypertension, and immunity?

Abstract: Background The association between oral dysbiosis and chronic kidney disease (CKD) has gained increasing attention in recent years. Diabetes and hypertension are the most common conditions in CKD. However, a case–control study with matched confounding variables on the salivary microbiome in CKD and the influence of diabetes and hypertension on the microbiome has never been reported. Methods In our study, we compared the salivary microbiome profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Prevotella and Haemophilus were decreased in CKD patients, whereas Streptococcus , Actinomyces , and Leptotrichia were enriched 59 . A new study has found a unique bacterial saliva microbiome in individuals with CKD, which is characterized by notable changes in its composition 60 …”
Section: Ckdmentioning
confidence: 96%
See 1 more Smart Citation
“…Prevotella and Haemophilus were decreased in CKD patients, whereas Streptococcus , Actinomyces , and Leptotrichia were enriched 59 . A new study has found a unique bacterial saliva microbiome in individuals with CKD, which is characterized by notable changes in its composition 60 …”
Section: Ckdmentioning
confidence: 96%
“…59 A new study has found a unique bacterial saliva microbiome in individuals with CKD, which is characterized by notable changes in its composition. 60…”
Section: Ramanathan Et Almentioning
confidence: 99%
“…The samples were added to 500 µL lysis bufer and stored at − 80 ℃ until DNA isolation. The procedures of DNA extraction, 16S rRNA quantitative PCR, qualitative 16S targeted metagenomic sequencing, and bioinformatic analysis are described in our previous study [14]. Notably, polymerase chain reaction (PCR) ampli cation of the bacterial 16S rRNA genes V3-V4 region was performed using the universal primers 319F and 806R with 30 cycles.…”
Section: Study Subjects' Enrollmentmentioning
confidence: 99%
“…However, the impact of imbalanced oral microbiota extends beyond oral health conditions. For instance, oral dysbiosis has been associated with various systemic disorders, including Alzheimer's disease [11], coronary artery disease [12], arthritis [13], chronic kidney disease [14], systemic lupus erythematous [15], and colitis etc. [16], are linked to the oral dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Saliva, one of the largest sources of gut microbiota, may play an important role in kidney disease that salivary microbiota ectopically colonizing the gut may be closely associated with the development of kidney disease and renal function. At the same time, several studies have discussed changes in salivary flora in patients with CKD (Hu et al, 2018 ; Duan et al, 2020 ; Guo et al, 2022 ; Liu et al, 2022 ). The overall composition of the salivary microbiota in CKD patients is significantly different from that of the healthy population, although the variation in individual flora or individual indicators is not entirely consistent across studies.…”
Section: Introductionmentioning
confidence: 99%